Analisis Metode Penerjemahan Dalam Menerjemahkan Novel Bumi Manusia - Mazaya, Fiki (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
This study aims to analyze the translation methods used in translating the novel Bumi Manusia by Pramoedya Ananta Toer, with a focus on cultural aspects, social interaction, and the complex social identity. The study employs a qualitative descriptive method. The data source consists of sentences from the novel Bumi Manusia by Pramoedya Ananta Toer. The results of the study indicate that there are three translation methods proposed by Peter Newmark, namely the communicative method (45.22%), the semantic method (32.60%), and the idiomatic method (22.18%). These three methods are able to preserve the cultural nuances within the context of early 20th-century Indonesia and also introduce the social values inherent in the colonial society structure. In translation, there are significant challenges in transferring culturally specific terms related to social status, such as